Cushioning material for glass plates and glass laminate

JP7643764B1Active Publication Date: 2025-03-11NAGARA SEISHI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024124829
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-11
Estimated Expiration
2044-07-31

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、重ねられたガラス板の間に保持される緩衝材料として、自然環境への悪影響が抑えられ、かつガラス板を重ねて保持するために必要な機能を有するものが得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643764000001_ABST
    Figure 0007643764000001_ABST
Patent Text Reader

Abstract

To obtain a buffer material to be held between overlapping glass plates, which has a reduced adverse effect on the natural environment and has properties required for holding the overlapping glass plates. [Solution] The buffer material for glass plates is interposed between glass plates, and is a powder containing 50% by weight or more of a water-soluble inorganic salt component. The preferred water-soluble inorganic salt particles are sodium chloride particles 303 having a cubic shape. The parallel flat faces of the sodium chloride particles 303 come into surface contact with the surfaces of the glass plates 301 and 302, and high adhesion is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a buffer material for placement between stacked glass sheets. [Background technology]

[0002] When transporting, storing, or handling glass plates, a buffer material is inserted between each of the multiple stacked glass plates to prevent scratches caused by contact between the glass plates. There is a technology that uses powder made of synthetic resin particles (beads) with particle diameters of several tens to several hundreds of μm as the buffer material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] U.S. Patent No. 10,611,546 Summary of the Invention [Problem to be solved by the invention]

[0004] There are concerns about the impact of the powder used as the buffer material on the environment. For example, when the powder is spread on the surface of a glass plate, the powder falls from the surface of the glass plate. The powder that falls from the glass plate is collected, but there is no guarantee that it is complete, and there is a risk that it will be released into the environment (for example, mixed with cleaning water and flowing into the sewer). In addition, the powder is removed from the surface of the glass plate during secondary processing of the glass plate (cutting or processing for commercialization), and the same risk exists at this time. In addition, although the amount is small, there is a possibility that the powder will scatter during transportation or transportation in the production process of the glass plate laminated via the powder.

[0005] From the viewpoint of protecting the natural environment, it is undesirable for synthetic resin powder to be released into the environment. For example, there are concerns about the adverse effects of the accumulation of synthetic resin powder on fish, shellfish, birds, and animals.

[0006] On the other hand, the glass sheets are required to have a high level of surface properties (flatness, absence of scratches and dirt), and in order to reliably protect the stacked glass sheets during transportation, the powder held between the glass sheets is also required to have high functionality (strength and retention).

[0007] In this context, the present invention aims to provide a highly functional material as a buffer material to be held between stacked glass sheets, and also aims to provide a material that has a minimal adverse effect on the natural environment and has the functionality required to hold stacked glass sheets together. [Means for solving the problem]

[0008] The present invention relates to a buffer material to be interposed between glass plates, the buffer material comprising cubic particles having a coating layer, the coating layer comprising water-soluble cellulose, and the particles being sodium chloride particles. and contains 50% by weight or more of the sodium chloride particle component. A buffer material for glass plates. The present invention is a buffer material to be interposed between glass plates, which is a powder containing 50% by weight or more of a component with a cubic crystal structure, and particles constituting the powder are sodium chloride particles having a cubic shape. In the present invention, the particles may have an equivalent circle diameter of 10 μm to 250 μm. In the present invention, the particles may have a cellulose coating layer.

[0009] The present invention relates to a glass laminate in which at least two glass sheets are laminated via a buffer material for glass sheets, the buffer material for glass sheets being a powder containing 50% by weight or more of sodium chloride particles having a cubic crystal structure. The present invention relates to a glass laminate in which at least two glass sheets are laminated via a buffer material for glass sheets, the buffer material for glass sheets being a powder containing 50% by weight or more of sodium chloride particles having a cubic crystal structure. More than 50% by weight of the above ingredients one of the two parallel planes is in contact with a surface of one of the two glass plates, and the other of the two parallel planes is in contact with a surface of the other of the two glass plates. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a buffer material to be held between stacked glass sheets, which has a reduced adverse effect on the natural environment and has the necessary functions for holding the stacked glass sheets. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a conceptual diagram of an embodiment. [Diagram 2] 1 is a drawing-substitute photograph showing a microscope photograph of sodium chloride particles. [Diagram 3] FIG. 2 is an image diagram showing a cross-sectional structure of a sodium chloride particle having a coating layer. [Figure 4] 1 is a drawing substitute photograph showing a microscope photograph of sodium chloride particles without a coating layer. [Diagram 5] 1 is a drawing-substitute photograph showing a microscope photograph of sodium chloride particles with a coating layer. [Figure 6] FIG. 1 is an image diagram showing a method for measuring adhesion to a glass plate. [Figure 7] 1 is a graph showing the results of measuring the adhesion of sodium chloride particles and acrylic resin particles to a glass plate. [Figure 8] FIG. 2 is an image showing the state of adhesion of cubic sodium chloride particles to a glass plate. [Figure 9] 1 is a graph showing the relationship between pressure applied to sodium chloride particles and the amount of deformation. [Figure 10] 1 is a graph showing the relationship between pressure applied to acrylic particles and the amount of deformation. [Figure 11] 1 is a graph showing the relationship between the pressure applied to a particle of mirabilite and the amount of deformation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] 1. First embodiment (overview) The powder of the buffer material for glass plates shown in this embodiment has the following characteristics. (1) It has little adverse impact on the environment. (2) High adhesion to glass plates due to the particle shape. (3) High dispersibility when applied to the surface of a glass plate. (4) Sufficient strength to hold the stacked glass sheets together. (5) The glass is less likely to get dirty. (6) Easy to clean.

[0013] 1 shows a state in which four glass plates 101, 102, 103, and 104 are stacked. The number of glass plates to be stacked is not limited, and two or more plates are possible. Here, four plates are shown as an example. The applications of the glass plates are not limited, and examples include architecture, vehicles, displays, and solar cells.

[0014] Between the glass plates 101 and 102, a particulate layer 111 is provided; between the glass plates 102 and 103, a particulate layer 112 is provided; between the glass plates 103 and 104, a particulate layer 113 is provided.

[0015] The particulate layer 111 functions as a buffer layer to prevent the glass plate 101 from coming into direct contact with the glass plate 102. The particulate layers 112 to 113 have the same function. The particulate layers 111 to 113 also have the function of holding the adjacent glass plates vertically so that they do not move relative to each other due to vibration or impact, and the function of absorbing vibration and impact. The thickness of the particulate layers 111 to 113 is about 10 μm to 400 μm, and preferably about 50 μm to 150 μm.

[0016] (Particles that make up the particle layer) The particle layers 111 to 113 are mainly composed of sodium chloride (NaCl) powder. Each of the particle layers 111 to 113 has a sodium chloride (NaCl) content of 50% by weight to 99.9% by weight, preferably 80% by weight to 99.9% by weight, and more preferably 95% by weight to 99.9% by weight, with the remainder being a coating layer that covers the sodium chloride particles, additives that are added as necessary, or unavoidable impurities.

[0017] The particles (sodium chloride particles) that make up the sodium chloride powder have a cubic (regular hexahedral) shape. Cubic sodium chloride particles are obtained by isotropic crystal growth. The cubic shape also includes shapes with rounded corners. In this case, a shape in which 80% or more of the surface is flat is preferable. The term "particle" refers to individual grains.

[0018] The particle size of the sodium chloride particles is determined as a circle equivalent diameter, and is 10 μm to 400 μm on average, and preferably 10 μm to 250 μm.. Fig. 2 is a microscope photograph of the sodium chloride particles used in this embodiment.

[0019] As shown in Fig. 2, the sodium chloride particles used in this embodiment have a cubic shape (dice shape). It is preferable that the particle size distribution of the sodium chloride powder is narrow (sharp). By narrowing the distribution width, the amount of unnecessary (small) particles that do not hold the glass can be reduced, making it more economical.

[0020] Sodium chloride has a sodium chloride type crystal structure, which is one of the cubic crystal structures. This crystal structure is the basic structure of a cubic (regular hexahedral) particle shape. The cubic sodium chloride particles used in this embodiment are obtained by isotropically growing the basic cubic crystal structure.

[0021] The cubic sodium chloride particles have parallel flat faces. These faces come into surface contact with the glass surface, and as described below, the powder made of the sodium chloride particles has high adhesion and cohesion to the glass plate. This effect is applicable to all particles obtained by isotropically growing a cubic crystal structure.

[0022] (Coating layer) The sodium chloride particles used in this embodiment are covered on the surface with a coating layer (covering layer) having biodegradability. Known biodegradable materials can be used as the biodegradable material used for the coating. An example of the biodegradable material is water-soluble cellulose. Here, an aqueous solution of water-soluble cellulose is spray-coated onto the surface of the sodium chloride particles to form a coating layer of water-soluble cellulose on the surface of the sodium chloride particles. The thickness of the coating layer when dried is 1 μm to 20 μm, preferably about 2 μm to 10 μm. The proportion of the water-soluble cellulose component in the coating layer is 50% by weight or more.

[0023] Spray coating is a method in which particles are suspended in an air flow to form a fluidized bed, and an aqueous solution containing a coating material is sprayed onto the fluidized bed to adhere the coating material to the particle surfaces and then dried to form a coating layer. In spray coating, the thickness of the coating layer can be controlled by adjusting the temperature and volume of the air flow to form the fluidized bed, and the concentration of the aqueous solution containing the coating material and the spraying conditions.

[0024] 3 is a cross-sectional image diagram of a sodium chloride particle 150 coated with a coating layer 151. By providing the coating layer 151, the dispersibility of the powder constituted by the sodium chloride particles 150 can be improved.

[0025] Figure 4 is a microscope photograph of sodium chloride particles without a coating layer scattered on a glass plate. Table 1 shows the particle size distribution of the sodium chloride particles without a coating layer in Figure 4.

[0026] [Table 1]

[0027] Figure 5 is a microscope photograph of sodium chloride particles with a coating layer sprinkled on a glass plate. Table 2 shows the particle size distribution of the sodium chloride particles with a coating layer in Figure 5.

[0028] [Table 2]

[0029] The coating layer in the case of Fig. 5 is a layer of water-soluble cellulose, and its thickness is about 4 µm. Here, "Metolose" (registered trademark) manufactured by Shin-Etsu Chemical Co., Ltd. was used as the water-soluble cellulose. The spray coating was performed using a fluidized bed device MP01 manufactured by Powrex Corporation.

[0030] As is clear from a comparison of FIG. 4 and FIG. 5, the dispersibility of sodium chloride particles is improved by providing a coating layer.

[0031] Table 3 shows data on the dispersibility of sodium chloride particles shown in Figure 4, which does not have a coating layer of water-soluble cellulose, on a glass plate. Here, sodium chloride powder was spread on a slide glass, images were taken with a microscope, and the dispersion rate was calculated after counting the number of particles. In Table 3, dispersed particles are particles that are separated (isolated), and agglomerated particles are particles in which two or more particles have aggregated and can be regarded as one particle, recognized as one particle.

[0032] Dispersion rate is the ratio of particles that can be considered as a single isolated particle to all particles to be measured on the glass plate. A dispersion rate of 100% occurs when all particles to be measured are observed as a single isolated particle. The higher the dispersion rate, the more uniformly the particles are distributed on the glass plate. The lower the dispersion rate, the greater the ratio of particles in a state where two or more particles are aggregated, and the greater the tendency for the particles to be distributed unevenly.

[0033] [Table 3]

[0034] Table 4 shows data on the dispersibility of sodium chloride particles having a water-soluble cellulose coating layer on a glass plate as shown in FIG. 5. The experimental conditions are the same as those in Table 3.

[0035] [Table 4]

[0036] Tables 3 and 4 show the high dispersibility of sodium chloride particles with a coating layer. Table 5 shows data on the dispersibility of acrylic powder. Table 6 shows the particle size distribution of the acrylic particles in Table 5. As shown in Table 5, the dispersibility of the acrylic particles is not as good as that of sodium chloride particles with a coating layer. In addition, acrylic particles are highly electrostatically charged, and in actual use, their dispersibility tends to be lower than the data in Table 5.

[0037] [Table 5]

[0038] [Table 6]

[0039] High dispersibility means that the powder has high fluidity. In the process of spreading the powder on the glass plate, it is desired that the powder can be spread with good dispersibility without agglomeration. If the dispersibility of the particles is poor, the retention layer that holds the stacked glass plates tends to be uneven (tend to be in patches). If the retention layer becomes uneven, partial gap spaces are generated, which increases the possibility of glass tarnish, and this is not preferable. In this regard, the effect of increasing the dispersibility of the particles by providing the above-mentioned coating layer is great.

[0040] The coating layer also has the function of preventing sodium chloride components from coming into direct contact with the glass sheet surface. Direct contact of sodium and chlorine components with the glass sheet surface can cause scale marks, which are scale-like patterns. By providing the coating layer 151, the occurrence of this problem can be suppressed.

[0041] Incidentally, there is a known problem of glass tarnish caused by the elution of alkaline components from inside the glass sheet onto the surface of the glass sheet. As a method for suppressing this phenomenon, there is a method for supplying alkaline components from the outside to the surface of the glass sheet to suppress the elution of alkaline components from inside the glass sheet. The coating layer 151 also functions as a buffer layer that realizes the appropriate supply of alkaline components from the sodium chloride particles 150 to the surface of the glass sheet. Therefore, the coating layer 151 has a function of preventing the occurrence of the above-mentioned scale-like marks caused by the material of the sodium chloride particles 150 themselves, and a function of suppressing the occurrence of glass tarnish by the appropriate supply of alkaline components to the surface of the glass sheet.

[0042] In addition to cellulose, organic acids (adipic acid, succinic acid, citric acid), water-soluble inorganic salts (mirabite, etc.), sodium acetate (sodium salt of an organic acid), PLA (biodegradable resin), etc., or a combination of two or more of these materials can be used as materials constituting the coating layer 151. A method for forming a coating layer of these materials includes a spray coating method.

[0043] The spray coating method can be used regardless of whether the material to be coated is water-soluble or not. If the material is water-soluble, an aqueous solution of the material is used as the spray solution. If the material is insoluble or poorly water-soluble, a liquid in which fine powder of the material is dispersed is used as the spray solution. For insoluble or poorly water-soluble materials, the particle size of the fine powder particles is 10% or less, preferably 5% or less, of the particle size of the base particle. In this case, a coating layer is formed in which many particles of the fine powder are attached to the surface of the base particle.

[0044] For example, suppose a coating layer of adipic acid is formed on cellulose particles with an average particle size of 150 μm. In this case, a coating layer of a desired thickness is formed by a spray coating method using a liquid containing adipic acid particles with an average particle size of 1 μm as the spray liquid. In this case, the surface of the cellulose particles is covered with a large number of adipic acid fine particles distributed in layers. The coating layer is formed by the large number of adipic acid fine particles distributed in layers.

[0045] The coating layer may also include a biodegradable material and a water-soluble inorganic salt and / or an organic acid. For example, the coating layer may be formed by a spray coating method using an aqueous solution containing water-soluble cellulose and water-soluble inorganic salts as the spray liquid, or by a spray coating method using an aqueous solution containing water-soluble cellulose and organic acid particles as the spray liquid.

[0046] (Adhesion to glass plate) Fig. 6 is an image diagram showing a method for measuring adhesion to a glass plate. In the method shown in Fig. 6, first, powder is scattered on a horizontal glass plate, and then the glass plate is held vertically and impacted with a hammer. The total area in photographed images of the powder adhering to the glass plate surface before and after the impact is determined by image analysis, and the particle residual rate is calculated by (total area of ​​particles adhering after impact) / (total area of ​​particles adhering before impact). The particle residual rate is the proportion of powder that did not fall off from the glass plate surface due to the impact.

[0047] figureTable 7 shows the measurement results of the particle residual rate of sodium chloride particles and acrylic particles (PMMA) on a glass plate. The horizontal axis is the hammer angle in FIG. 6. Table 7 shows the measurement results on which FIG. 7 is based. The hammer angle corresponds to the impact acceleration applied to the glass plate. The larger the hammer angle, the larger the impact acceleration applied to the glass plate. According to the findings of the present inventors, as a guideline, the impact acceleration applied to the glass plate at a hammer angle of 30° is 100G, the impact acceleration applied to the glass plate at a hammer angle of 45° is 390G, and the impact acceleration applied to the glass plate at a hammer angle of 60° is 680G.

[0048] [Table 7]

[0049] The sodium chloride particles used had the particle shape shown in Figure 2 and the particle size distribution shown in Table 1. The PMMA sample used had the particle size distribution shown in Table 6. Note that the sample in Figure 7 did not have a biodegradable coating layer.

[0050] PMMA powder is currently used in the industry as a buffer material for glass plates. Results Therefore, it can be said that sodium chloride particles having the particle shape shown in Figure 2 have a high adhesiveness equal to or higher than the appropriate adhesiveness of PMMA.

[0051] (Considerations regarding adhesion) Fig. 8 is an image diagram showing the state of particles adhering to a glass plate. Fig. 8(A) shows a state in which a spherical particle 203 (e.g., an acrylic particle) is held between glass plates 201 and 202. Fig. 8(B) shows a state in which a cubic particle 303 (e.g., a sodium chloride particle) is held between glass plates 301 and 302.

[0052] In the case of Figure 8(A), the contact of the particles with the glass plate is close to point contact. In contrast, in the case of Figure 8(B), the contact of the particles with the glass plate is surface contact. For the same material, the adhesive force of the particles to the glass plate surface increases as the contact area increases. When considering the contribution to adhesive force, the difference between the above point contact and surface contact is large, and this is thought to be the reason for the good adhesion (high adhesive force) of sodium chloride powder to glass plates.

[0053] In particular, cubic particles have three sets of parallel flat surfaces that cross each other at right angles, and ideally have the same area, so that the two flat surfaces of each particle are highly likely to come into contact with the opposing glass surface, resulting in particularly high adhesion to the glass surface, and therefore high adhesion to the glass surface.

[0054] (particle strength) The deformation strength was measured as particle strength. In elastic-plastic or malleable materials, deformation often continues without breaking. Therefore, focusing on the degree of deformation, the applied force when compressively displaced by 50% of the particle diameter was measured as the deformation strength.

[0055] The measurement was carried out on 10 samples using a microparticle crushing force measuring device (NS-A300 model manufactured by Nanoseeds Co., Ltd.). In the measurement, the particles were pressed into the crushing needle, and a waveform chart of the pressing force at this time was recorded. The amount of deformation was also measured from the displacement of the crushing needle.

[0056] The deformation strength is σ 10% =F 10% / A (JIS Z 8844), where σ 10% is the deformation strength (Pa) for a compressive displacement of 10% of the particle diameter. F 10% is the test force (N) for a compressive displacement of 10% of the particle diameter. A is the area (m 2 ) The particle size was measured by image analysis. Here, the deformation strength σ 50% The measurement data related to the particle strength are shown in Table 8. The measurement was performed on particles without a coating layer.

[0057] [Table 8]

[0058] Acrylic particles are used as a buffer material for glass plates. Figures 9 to 11 are graphs showing the relationship between the force (vertical axis) of the crushing needle for each particle measured by the above-mentioned microparticle crushing force measuring device and the deformation amount of the particle. Here, Figure 9 shows data for sodium chloride particles, Figure 10 shows data for acrylic particles, and Figure 11 shows data for Glauber's salt particles. It can be seen that the sodium chloride particles in Figure 9 and the acrylic particles in Figure 10 are deformed in approximately proportion to the pushing force. The disturbance of the waveform in the data for Glauber's salt particles in Figure 11 indicates the state in which the particles are broken by pressure. From these, it can be said that sodium chloride particles have sufficient strength required for a buffer material for glass plates.

[0059] Moreover, the sodium chloride particles in Fig. 9 show deformation closer to elastic deformation than the acrylic particles in Fig. 10. This means that when used as a buffer material for glass plates, the sodium chloride particles can more effectively absorb shocks and vibrations applied to the laminate of glass plates than the acrylic particles.

[0060] Example 1 For the particle layers 111 to 113 in FIG. 1, sodium chloride powder having the particle shape shown in FIG. 2 and the particle size distribution in Table 2 was used.

[0061] The particles (sodium chloride particles) constituting this sodium chloride powder are formed by spray-coating the surface of the sodium chloride particles with an aqueous solution of water-soluble cellulose to form a coating layer of water-soluble cellulose. The thickness of the coating layer (when dry) was 4 μm. As the water-soluble cellulose, "Metolose" (registered trademark) manufactured by Shin-Etsu Chemical Co., Ltd. was used. The spray coating was performed using a fluidized bed device MP01 manufactured by Powrex Corporation.

[0062] Example 2 Table 9 To , acrylic particles and sodium chloride particles without coating layer Indicates measurement values ​​such as deformation strength. The sodium chloride particles have a cubic appearance as shown in Figure 2. The average adhesive strength is the adhesive strength to a glass plate.

[0063] The adhesion was measured using a centrifugal adhesion measuring device (NS-C100 model manufactured by Nano Seeds Co., Ltd.). In this measurement, the sample was attached to the surface of a substrate (glass plate), and then the substrate was centrifuged at six levels of 100G to 800G in a centrifuge, the state of particle separation was recorded as an image, and the particle residual rate after rotation was measured against the initial number of particles attached before centrifugation.

[0064] The adhesion force of a particle to the substrate is equal to the centrifugal separation force acting on the particle, F = (π / 6)ρd 3 rω 2 Here, ρ is the true density of the particles, d is the particle diameter, r is the rotation radius of the centrifuge, and ω is the rotation angular velocity of the centrifuge. The particle residual rate after rotation was plotted on the horizontal axis, and the separation force of the particles at each rotation part was plotted on the vertical axis, and the average adhesion force (separation force at which 50% of the particles separate) was calculated from the exponential approximation curve.

[0065] [Table 9]

[0066] From Table 9, it can be seen that the sodium chloride particles have high strength and show good adhesion to the glass plate.

[0067] Example 3 The test shown in Figure 6 was carried out on sodium chloride particles with a water-soluble cellulose coating layer in Table 2 and sodium chloride particles without a coating layer in Table 1. Tables 10 and 11 show the test results (particle residual rate).

[0068] [Table 10]

[0069] [Table 11]

[0070] The adhesion of sodium chloride particles with a coating layer to glass plates is lower than that of particles without a coating layer. However, the impact tests at hammer angles of 45° and 60° are fairly severe test conditions, and it is believed that sodium chloride particles with a coating layer also have adhesion to practical impacts.

[0071] Example 4 It is also possible to incorporate organic acid particles into the coating layer of the sodium chloride particles. 、 The particle size of the organic acid is set to be equal to or smaller than the thickness of the coating layer. For example, the coating layer is composed of fine powder of water-soluble cellulose and adipic acid. The base particles are sodium chloride particles shown in Table 1. The coating layer is formed by a spray coating method using a mixture of an aqueous solution of water-soluble cellulose and adipic acid having an average particle size of 2 μm as a spray liquid. The thickness of the coating layer is set to be approximately 5 μm. The mixture ratio of water-soluble cellulose and adipic acid is 90:10 to 99:1, for example 95:5, in terms of weight ratio when dried.

[0072] In this example, the adipic acid particles are incorporated into a coating layer of water-soluble cellulose. This coating layer structure is expected to provide high dispersibility due to the coating layer, and the incorporated adipic acid particles are expected to prevent glass tarnish and improve adhesion to glass plates.

[0073] Example 5 The coating layer is made of fine powder of organic acid. In this example, the coating layer is made of fine powder of adipic acid. The base particles are sodium chloride particles in Table 1. The coating layer is formed by the spray coating method, and the spray liquid contains adipic acid with an average particle size of 1 μm. The thickness of the coating layer is about 5 μm. In this example, the coating layer is formed by many adipic acid particles distributed in a shell shape.

[0074] (Advantages) Sodium chloride powder has the following advantages as a buffer material for glass plates: (1) It has little adverse impact on the environment. (2) High adhesion to glass plates due to the particle shape. (3) High dispersibility when applied to the surface of a glass plate. (4) Sufficient strength to hold the stacked glass sheets together. (5) The glass is less likely to get dirty. (6) Easy to clean.

[0075] Sodium chloride is a natural substance that exists in nature and has less of a negative impact on the environment than synthetic resin particles.

[0076] A powdered buffer material for glass plates is required to have high adhesion to glass plates. In this regard, as shown in Fig. 8, a cubic sodium chloride particle 303 has parallel flat faces that come into surface contact with the surfaces of glass plates 301 and 302, and therefore has high adhesion.

[0077] Current acrylic powders have the problem of poor dispersibility on glass plates (see Table 5). If the powder disperses poorly on glass plates, the powder will not be distributed uniformly between the stacked glass plates, forming gaps in parts where the particle layer is absent. If stacked glass plates are stored for a long period of time, there is a risk of glass discoloration occurring in these gaps. Sodium chloride powder with a coating layer formed has high dispersibility, which prevents the problems caused by the presence of the non-uniform particle layer described above.

[0078] In addition, the particles of the glass sheet buffer material composed of powder need to be strong. This is because if the particles break due to the pressure when the glass sheets are stacked, contact between the glass sheets and damage to the glass sheet surfaces will occur. The cubic sodium chloride particles are crystalline and have the strength required for a glass sheet buffer material.

[0079] By providing a coating layer of water-soluble cellulose on the surface of sodium chloride particles, the sodium chloride component does not come into direct contact with the glass. but This prevents the glass from being contaminated by sodium chloride. In addition, sodium chloride can be easily removed from the glass surface by washing with water, making cleaning easy.

[0080] 2. Other embodiments Particles having a sodium chloride type crystal structure include magnesium oxide particles. Particles having a cubic crystal structure include alum (potassium alum, etc.). These particles are also obtained by isotropically growing a basic crystal structure. These particles also have flat surfaces, and can provide good adhesion to glass plates similar to the above-mentioned sodium chloride particles. The particle size, formation of a coating layer, etc. are the same as those described in the specification. Magnesium oxide and alum are naturally occurring substances in the natural world, and do not have adverse effects on the environment like synthetic resins. It is also possible to use a mixture of two or more of sodium chloride particles, magnesium oxide particles, and alum particles.

[0081] 3.Other It is also possible to dry and charge a powder composed of particles having a cubic crystal structure as exemplified in this specification. By drying and charging the powder, the adhesion to the glass plate can be improved.

[0082] As shown in Tables 10 and 11, sodium chloride particles provided with a coating layer of water-soluble cellulose show reduced adhesion to glass plates compared to particles without the coating layer. One possible method for suppressing this reduction is to hydrophobize the coating layer of water-soluble cellulose. Hydrophobization makes it difficult for moisture to be adsorbed, increasing electrostatic charge. This improves adhesion to glass plates. Examples of treatments for hydrophobizing include fluorine plasma treatment and plasma treatment in a reducing atmosphere of a hydrocarbon (e.g., methanol).

[0083] Various additives can be used. These additives can be (1) mixed as particles, (2) As mentioned earlier The aqueous solution containing the additive is mixed with a coating liquid for forming a coating layer made of a biodegradable resin. , and form them on the surface of the base particle. (3) In addition to the coating layer made of a biodegradable resin, a coating layer can be formed on the surface of the base particle using an aqueous solution or sol containing the additive.

[0084] According to the technology disclosed in this specification, it is possible to obtain a glass laminate that has a reduced impact on the natural environment and meets the requirements for holding glass sheets stacked together. The invention disclosed in this specification is described below. The invention disclosed in this specification is a buffer material for glass plates to be interposed between glass plates, the buffer material comprising cubic particles having a coating layer. An example of the buffer material is one in which the coating layer comprises water-soluble cellulose and the particles are sodium chloride particles. The invention disclosed in this specification is a buffer material for glass plates, which is a powder containing 50% by weight or more of a component with a cubic crystal structure. The particles constituting the powder may have a sodium chloride crystal structure. The particles constituting the powder may have a cubic shape. The particles constituting the powder may have two parallel planes. The particles constituting the powder may have a flat surface. The particles constituting the powder may be at least one of sodium chloride particles, magnesium oxide particles, and alum particles. The particles constituting the powder may have a circle equivalent diameter of 10 μm to 250 μm. The surfaces of the particles constituting the powder may be covered with a coating layer having biodegradability. The coating layer may contain water-soluble inorganic salts and / or organic acids. The particles constituting the powder are sodium chloride particles, the surfaces of the particles constituting the powder are covered with a coating layer of water-soluble cellulose, and when the powder is dispersed on a glass plate, isolated particles are considered to be dispersed particles, and the dispersion rate is defined as (number of dispersed particles / total number of particles), and an example of an embodiment in which the dispersion rate of the powder is 80% or more. The invention disclosed in this specification is a cushioning material for glass plates to be interposed between glass plates, which is a powder containing 50% by weight or more of particles having a cubic shape. The invention disclosed in this specification is a buffer material for glass plates to be interposed between glass plates, the buffer material being a powder containing 50% or more by weight of particles having a cubic crystal structure and having a cubic shape due to isotropic growth of the cubic crystal structure. The invention disclosed in this specification is a glass laminate in which at least two glass plates are laminated together via a buffer material for glass plates, the buffer material for glass plates being a powder containing 50% by weight or more of components with a cubic crystal structure. The invention disclosed in this specification is a glass laminate in which at least two glass plates are laminated via a buffer material for glass plates, the buffer material for glass plates being a powder containing particles having two parallel planes, one of the two parallel planes being in contact with a surface of one of the two glass plates, and the other of the two parallel planes being in contact with a surface of the other of the two glass plates. The particles constituting the powder may be at least one of sodium chloride particles, magnesium oxide particles, and alum particles. [Explanation of symbols]

[0085] 101...glass plate, 102...glass plate, 103...glass plate, 104...glass plate, 111...particle layer, 112...particle layer, 113...particle layer, 150...sodium chloride particles, 151...coating layer, 201...glass plate, 202...glass plate, 203...spherical particles, 301...glass plate, 302...glass plate, 303...cubic-shaped particles (sodium chloride particles).

Claims

1. A buffer material to be interposed between glass sheets, the buffer material comprising cubic particles having a coating layer; the coating layer comprises water-soluble cellulose; the particles are sodium chloride particles, A buffer material for glass plates containing 50% by weight or more of the sodium chloride particle component.

2. A buffer material to be interposed between glass plates, the buffer material being a powder containing 50% by weight or more of a component having a cubic crystal structure; The particles constituting the powder are sodium chloride particles having a cubic shape.

3. 3. The buffer material for glass plates according to claim 1, wherein the particles have an equivalent circle diameter of 10 μm to 250 μm.

4. 3. The buffer material for glass plates according to claim 2, wherein the particles have a coating layer of cellulose.

5. A glass laminate in which at least two glass plates are laminated via a buffer material for glass plates, The glass laminate, wherein the buffer material for glass sheets is a powder containing 50% by weight or more of sodium chloride particles having a cubic crystal structure.

6. A glass laminate in which at least two glass plates are laminated via a buffer material for glass plates, The buffer material for glass plates is a powder containing 50% by weight or more of sodium chloride particles having two parallel planes, A glass laminate in which one of the two parallel planes is in contact with a surface of one of the two glass plates, and the other of the two parallel planes is in contact with a surface of the other of the two glass plates.

Citation Information

Patent Citations

  • sensor

    JP1991053112A

  • Peeling agent

    JP1993294664A

  • Shipping system for shipping glass sheets

    US10611546B2

  • Shock-absorbing spacer for sheet glasses and stacked glass sheets

    WO1999033757A1

  • Interleavant particles for location between stacked glass sheets

    WO2022148947A1